2021
DOI: 10.1038/s42003-021-01668-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural dimethyl sulfide gradients would lead marine predators to higher prey biomass

Abstract: Finding prey is essential to survival, with marine predators hypothesised to track chemicals such as dimethyl sulfide (DMS) while foraging. Many predators are attracted to artificially released DMS, and laboratory experiments have shown that zooplankton grazing on phytoplankton accelerates DMS release. However, whether natural DMS concentrations are useful for predators and correlated to areas of high prey biomass remains a fundamental knowledge gap. Here, we used concurrent hydroacoustic surveys and in situ D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…For example, mysticetes might use dimethyl sulfide (DMS) as an olfactory indicator of their prey (Bouchard et al, 2019). Zooplankton biomass is spatially correlated to natural DMS concentrations in air, suggesting that particularly over broad geographic scales, DMS could act as a useful foraging cue for zooplankton predators, like mysticetes (Owen et al, 2021). Marine plastic can also emit DMS (Savoca, Wohlfeil, Ebeler, & Nevitt, 2016), which might disturb their foraging attempts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mysticetes might use dimethyl sulfide (DMS) as an olfactory indicator of their prey (Bouchard et al, 2019). Zooplankton biomass is spatially correlated to natural DMS concentrations in air, suggesting that particularly over broad geographic scales, DMS could act as a useful foraging cue for zooplankton predators, like mysticetes (Owen et al, 2021). Marine plastic can also emit DMS (Savoca, Wohlfeil, Ebeler, & Nevitt, 2016), which might disturb their foraging attempts.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that the olfactory sense is still functional in mysticetes but that it has partly been lost in odontocetes. A recent oceanographic survey in North Atlantic waters interestingly confirmed that DMS a and DMS g would accurately lead zooplankton predators such as mysticetes towards prey aggregations over long distances (Owen et al, 2021). The authors of the study however found no correlation between DMS (in air or in seawater) and fish biomass, possibly due to time lags between DMS production and the buildup of fish biomass.…”
Section: Discussionmentioning
confidence: 88%
“…The presumed short-scale attraction of the dolphins toward the DMS diffuser would however more likely be a curiosity response than a foraging behavior. The DMS test solution was much more concentrated than natural seawater (0.2 M vs. less than 20 nM, Turner, Malin, Nightingale, & Liss, 1996;Owen et al, 2021). We chose this concentration as it was previously shown to attract seabirds in the wild (Dell'Ariccia et al, 2014;Nevitt et al, 1995;Wright, Pichegru, & Ryan, 2011) and to induce an acoustic reaction in humpback whales (Bouchard et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations